Robust control for disturbed buck converters based on two GPI observers. (September 2017) - Wang, Zuo; Li, Shihua; Wang, Junxiao; Li, Qi
Abstract: The output voltage tracking problem of a disturbed buck converter is investigated in this paper via a GPI observer-based approach. Control performances of the converters are always influenced by undesirable effects of disturbances. These disturbances usually are of time-varying forms. Conventional backstepping schemes cannot achieve satisfactory performances in handling time-varying disturbances. By adding integral actions into the controller, only the slow-varying disturbances are asymptotically compensated in this way. In this paper, two GPI observers are constructed to estimate the lumped time-varying disturbances. By introducing the disturbance estimations into the design process, a composite GPI observer-based robust control scheme is developed. The proposed algorithm performs a promising disturbance rejection ability. Rigorous stability is guaranteed. Experimental results in the presence of time-varying disturbances are illustrated to show the feasibility of the proposed composite method. Highlights: A GPI observer-based robust controller is developed for Buck converter. Time-varying load variations and input voltage fluctuations are considered. High estimation precision is achieved by utilizing GPI observers. Disturbance effects are removed without sacrificing nominal performances.